27.1k views
1 vote
How do I solve for the variable? 3(x-14) + 1= -4x + 5

2 Answers

1 vote

The answer is 46/7.


First you distribute. So it would be 3x-42. Now add the 1 to the 42. your equation should look like 3x-43=-4x+5. Now add 4x to both sides. 7x-43=5. Now add -43 to both sides. Which is -37. Once you divide (don't ask about the division lol) you should get 46/7.


User YvetteLee
by
5.3k points
3 votes

Answer:

3·(x - 14) + 1 = - 4·x + 5

3·x - 42 + 1 = - 4·x + 5

3·x - 41 = - 4·x + 5

7·x - 41 = 5

7·x = 46

x = 46/7

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.